2018
DOI: 10.7307/ptt.v30i2.2344
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Oblique Pedestrian Streams

Abstract: The intersecting of pedestrian streams is a common phenomenon which would lead to the pedestrian deceleration, stopping, and even threat to the safety of walking. The organization of pedestrian flow is a critical factor which influences the intersection traffic. The aim of this paper is to study the characteristics of oblique pedestrian streams by a set of pedestrian experiments. Two groups of experiment participants, three volume levels and five intersecting angles were tested. The qualitative analysis and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 19 publications
4
4
0
Order By: Relevance
“…These findings are consistent with previous studies on merging intersections, where a reduced pedestrian flow rate for higher merging angles was observed [8,26]. However, in a study with oblique pedestrian streams [41], it was observed that a lower intersecting angle does not necessarily have better flow transition compared to a higher intersecting angle and that it depends on the pedestrian volumes in the intersecting streams. However, the experiment was conducted only with normal walking speed.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings are consistent with previous studies on merging intersections, where a reduced pedestrian flow rate for higher merging angles was observed [8,26]. However, in a study with oblique pedestrian streams [41], it was observed that a lower intersecting angle does not necessarily have better flow transition compared to a higher intersecting angle and that it depends on the pedestrian volumes in the intersecting streams. However, the experiment was conducted only with normal walking speed.…”
Section: Discussionsupporting
confidence: 91%
“…Despite this contradictory finding, it is to be noted that, in high density crowds and long intersecting blocked vision corridors, participants may not be able to anticipate the flow and speed at which the participants will enter the junction, which may influence the regulation of flow at the junction. Further, a study has shown differing performance of intersecting angles with different volumes of crossing pedestrians with un-blocked vision [41]. Therefore, in future, it is suggested to conduct additional experiments with different flow ratios (rather than two nearly equal flows), longer corridors, and different volumes of participants to further investigate the effect of blocked and un-blocked vision conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of oblique pedestrian streams were studied by Sun et al [37] quantitatively and qualitatively by varying the pedestrian volume levels and intersecting angles. A total of five intersection angles, i.e., 30 • , 60 • , 90 • , 120 • , and 150 • , were considered in this study and showed that, for low flow rates, 30 • was more efficient compared to the other angles.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, the placement of obstacle in the middle of the intersection could stabilize the intersecting flows. Sun et al (2017) and Sun et al (2018) further investigated the impact of intersecting angles and obstacle effects on intersecting movements[149,158]. It was found that the effects of angles on flow speed vary at different flow conditions.…”
mentioning
confidence: 99%